A retrospective study of fecal output and postprocedure colic in 246 horses undergoing standing sedation with detomidine, or general anesthesia with or without detomidine. (July 2019) - Thibault, Christopher J.; Wilson, Deborah V.; Robertson, Sheilah A.; Sharma, Dhruv; Kinsley, Marc A.
Abstract: Objective: To determine time to first passage of feces, total fecal piles and incidence of colic in the first 24 hours postprocedure in horses undergoing standing sedation with detomidine, or general anesthesia with or without detomidine. Study design: Retrospective cohort study. Animals: A total of 246 horses. Methods: Records of all horses that underwent standing sedation or general anesthesia between December 2012 and March 2016 were reviewed. Horses aged <6 months, admitted for colic or cesarean section, with inadequate data, and those not administered xylazine and/or detomidine were excluded. Records included patient signalment, fasting duration, procedure performed, drugs administered, time to first feces, number of fecal piles during 24 hours postprocedure and mention of colic. Chi-square, Fisher's exact and Tukey's post hoc comparison tests were used. Parametric data were reported as mean ± standard deviation with significance defined as p <0.05. Results: In total, 116 and 57 horses underwent general anesthesia without detomidine (group GA) and with detomidine (group GA–D), respectively, and remaining 73 horses underwent standing sedation with detomidine (group S–D). Detomidine dose was significantly higher in group S–D than in group GA–D. Time to first feces was longer (7.1 ± 4.2 hours), and group S–D horses passed one fewer fecal pile (6.3 ± 2.4) than group GA horses. There was no interaction between detomidine treatment and preprocedure food withholding and the time to first feces or the number of fecal piles in the first 24 hours postprocedure. Overall, seven horses (2.8%) showed signs of colic (five, one and one in GA, GA–D and S–D, respectively). Conclusions and clinical relevance: Detomidine administration, as part of an anesthetic protocol or for standing sedation procedures, should not be expected to contribute to postprocedural colic.